2014
DOI: 10.1088/1741-2560/11/2/024001
|View full text |Cite
|
Sign up to set email alerts
|

Pre-frontal control of closed-loop limbic neurostimulation by rodents using a brain–computer interface

Abstract: Objective There is great interest in closed-loop neurostimulators that sense and respond to a patient’s brain state. Such systems may have value for neurological and psychiatric illnesses where symptoms have high intraday variability. Animal models of closed-loop stimulators would aid preclinical testing. We sought to demonstrate that rodents can directly control a closed-loop limbic neurostimulator via a brain-computer interface (BCI). Approach We trained rats to use an auditory BCI controlled by single uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 48 publications
1
15
1
Order By: Relevance
“…The notion of creating artificial links to overcome neural circuit damage is proving to be especially effective in brain-machine-brain interfaces (BMBIs) 32 . These electronic devices composed of electrodes and computers, monitor and decode neural signals from one brain region, and then encode and deliver corresponding stimulation to a second region 33 . Such systems appear to be capable of bridging disconnected neural pathways, and thus restoring function after neural damage 34,35 .…”
Section: Discussionmentioning
confidence: 99%
“…The notion of creating artificial links to overcome neural circuit damage is proving to be especially effective in brain-machine-brain interfaces (BMBIs) 32 . These electronic devices composed of electrodes and computers, monitor and decode neural signals from one brain region, and then encode and deliver corresponding stimulation to a second region 33 . Such systems appear to be capable of bridging disconnected neural pathways, and thus restoring function after neural damage 34,35 .…”
Section: Discussionmentioning
confidence: 99%
“…Our group recently demonstrated platform technology for an alternate approach, where patients directly control the stimulator by thinking about what they want it to do (Widge et al, 2014; Widge & Moritz, 2014). A patient would evaluate whether the current simulation parameters (particularly the intensity of stimulation) match his/her needs, and could then volitionally modulate the stimulation parameters.…”
Section: Ongoing Challenges and Limitations Of Closed-loop Approachesmentioning
confidence: 99%
“…The patient would only receive treatment when they explicitly will it, making this a more personalized treatment compared to more traditional concepts of closed-loop stimulation. In rodent models, we have shown that animals can use this type of intentional control to trigger brain stimulation to the medial forebrain bundle (MFB), a reward center that is also a DBS target for MDD (Widge & Moritz, 2014). There would be much work to translate such a device to the clinic, including identifying a DBS target and stimulation regime that caused noticeable and immediate symptom relief.…”
Section: Ongoing Challenges and Limitations Of Closed-loop Approachesmentioning
confidence: 99%
“…The patient's signals in the recorded area would then 'tune' the DBS intervention as needed. We recently showed that rodents can learn to use prefrontal cortex signals in precisely this fashion to activate DBS-like stimulation (Widge and Moritz, 2014). Similar strategies may be useful for modulating fear behaviors in anxiety disorders, using fronto-limbic networks as targets (Besnard and Sahay, 2015).…”
Section: Acknowledgmentsmentioning
confidence: 99%